Results on non local impulsive implicit Caputo-Hadamard fractional differential equations - K. Venkatachalam; M. Sathish Kumar; P. Jayakumar (Mathematical Modelling and Control)
The results for a new modeling integral boundary value problem using Caputo-Hadamard impulsive implicit fractional differential equations with Banach space are investigated, along with the existence and uniqueness of solutions. The Krasnoselskii fixed-point theorem, Schaefer's fixed point theorem and the Banach contraction principle serve as the basis of this unique strategy, and are used to achieve the desired results. We develop the illustrated examples at the end of the paper to support the validity of the theoretical statements.